D-Ribose Induces Podocyte NLRP3 Inflammasome Activation and Glomerular Injury via AGEs/RAGE Pathway - Hong, Jinni; Li, Guangbi; Zhang, Qinghua; Ritter, Joseph; Li, Weiwei; Li, Pin-Lan (Frontiers in Cell and Developmental Biology, 2019)
D-ribose levels are demonstrated to be increased in type II diabetes mellitus and increased blood D-ribose is involved in the development of diabetic complications such as diabetic encephalopathy and nephropathy. However, the mechanism mediating the pathogenic role of D-ribose in nephropathy remains poorly understood. Given that D-ribose was reported to induce advanced glycation end products (AGEs) formation, the present study tested whether D-ribose induces NLRP3 activation and associated glomerular injury via AGEs/ receptor of AGEs (RAGE) signaling pathway. In vivo, C57BL/6J and Asc-/- mice were treated with D-ribose with or without AGEs inhibitor. Administration of D-ribose daily for 30 days was found to induce NLRP3 inflammasome formation in glomerular podocyte, as shown by increased co-localization of NLRP3 with apoptosis-associated speck-like protein containing a caspase recruitment domain (ASC) or caspase-1. This D-ribose-induced NLRP3 inflammasome formation was accompanied by its activation as evidenced by increased IL-1β production, a major product of NLRP3 inflammasome. Corresponding to NLRP3 inflammasome activation, D-ribose led to significant glomerular injury in mice. All these D-ribose-induced glomerular inflammasome and associated pathological changes were markedly attenuated by deletion of Asc gene. Futhermore, the accumulation of AGEs and RAGE was found increased in glomeruli of mice receiving D-ribose. In cell studies, we also confirmed that D-ribose induced NLRP3 inflammasome formation and activation in podocytes, which was significantly blocked by caspase-1 inhibitor, YvAD. Mechanically, AGEs formation inhibition and cleavage or silencing of RAGE gene were shown to suppress D-ribose-induced NLRP3 inflammasome formation and activation, as shown by significant reduction of NLRP3 inflammasome molecular aggregation, capsase-1 activity and IL-1β production. These results strongly suggest that relatively long term administration of D-ribose induces NLRP3 inflammasome formation and activation in podocytes via AGEs/RAGE signaling pathway, which may be one of important triggering mechanisms leading to diabetic nephropathy.